Formation of Readiness of Future Teachers of the Republic of Kazakhstan for Implementation of Education in the Inclusive Environment - Nurmaganbetova, Raugash K.; Kaldybayeva, Aychurek T.; Sartbekova, Nurjan K.; Umirbekova, Ayzat K.; Akhmetshin, Elvir M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The study aims to explore the readiness of future teachers for the implementation of education in the inclusive environment. Background: Inclusive education, which is intensively included in the practice of the modern school, raises many complex issues and new challenges. The teachers need specialised training in the field of correctional pedagogy to provide professional assistance and training for children with the oppositional defiant disorder. Method: The main method of research in the article is the study of literature on the research problem and a questionnaire survey method which was participated by 247 teachers of comprehensive schools of Karaganda Region. Results: During the analysis of the results of the survey, it was noted that many teachers were not ready for full and optimal communication with children with disabilities in development. The authors identified the conditions for the formation of professional and personal readiness of the teacher to work with children with disabilities. Conclusion: The transition to inclusive education requires the participation of all specialists of the education system and the availability of fundamental theoretical developments. The main problems of teachers who will have to work in the environment of inclusion are related to their theoretical training and practical skills of teaching this contingent of children.